2014
DOI: 10.1042/cs20130769
|View full text |Cite
|
Sign up to set email alerts
|

Human pleural B-cells regulate IFN-γ production by local T-cells and NK cells in aMycobacterium tuberculosis-induced delayed hypersensitivity reaction

Abstract: DTH (delayed type hypersensitivity) reactions are secondary cellular immune responses that appear 24-72 h after antigen exposure. Tuberculous pleurisy is a common manifestation of extrapulmonary TB (tuberculosis) and is considered a human model of Th1-mediated DTH. In order to identify functional cross-talk among cellular populations sited in this inflammatory microenvironment, we analysed phenotypic and functional features of human B-cells isolated from the PF (pleural fluid) of TB patients. Freshly isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…To make a wide characterization of blood B‐cell subsets circulating in ANDV + patients, we performed immunophenotyping based on CD27/IgD expression among CD19 + CD3 neg gated lymphocytes/lymphoblasts . The percentages of naive B cells – defined by surface IgD expression and lack of CD27 – were strongly reduced in ANDV + patients when compared with HS or with ARS patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To make a wide characterization of blood B‐cell subsets circulating in ANDV + patients, we performed immunophenotyping based on CD27/IgD expression among CD19 + CD3 neg gated lymphocytes/lymphoblasts . The percentages of naive B cells – defined by surface IgD expression and lack of CD27 – were strongly reduced in ANDV + patients when compared with HS or with ARS patients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For experiments described in Fig. , a group of patients with pulmonary tuberculosis (TB; n = 10; mean age 31 years, range 19–43 years) were enrolled and diagnosed at the Muñiz Hospital, as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the signaling axis through this pathway is identical regardless of the type of infection, the outcome is substantially different, suggesting that the type I IFNs and the related IFN-inducible genes are able to create a favorable or unfavorable intracellular milieu to promote or disrupt the survival of invading pathogens [16]. Changes in mRNA levels of IFIT1, IFIT2, CXCR3 and CD163 have been validated by qPCR in previous studies [17][18][19]. Moreover, Kim et al [20] confirmed that five genes (IFN-γ, TNF-α, IL-2R, CXCL9, and CXCL10) could be used for the detection of Mtb infection, including active PTB disease and LTB with sensitivity of each gene above 80%.…”
Section: Discussionmentioning
confidence: 85%
“…CXCR3 + B cells have previously been associated with migration to inflamed tissue [34][35][36][37] and may secrete interferon c (IFNc) 38 similar to their CD4 T cell counterpart; CXCR3 + Th1 cells. CXCR3 (CD183) ligands include the IFN-induced chemokines CXCL9 (MIG) and CXCL10 (IP-10), which have been shown to be systemically increased in high-risk populations.…”
Section: Discussionmentioning
confidence: 99%